2014
DOI: 10.1097/qai.0000000000000370
|View full text |Cite
|
Sign up to set email alerts
|

Depression During Pregnancy and the Postpartum Among HIV-Infected Women on Antiretroviral Therapy in Uganda

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 75 publications
5
64
2
Order By: Relevance
“…In addition, while other studies in sub-Saharan Africa have also found reductions in depressive symptoms at 12-months after ART initiation, our findings demonstrate a more rapid change in depressive symptoms as well as a decline in HIV-related stigma and an increase in social support during study follow-up (39,41,42). ART use may mitigate depressive symptoms by acting through psychological, behavioral, or biological pathways (39,4145).…”
Section: Discussioncontrasting
confidence: 47%
“…In addition, while other studies in sub-Saharan Africa have also found reductions in depressive symptoms at 12-months after ART initiation, our findings demonstrate a more rapid change in depressive symptoms as well as a decline in HIV-related stigma and an increase in social support during study follow-up (39,41,42). ART use may mitigate depressive symptoms by acting through psychological, behavioral, or biological pathways (39,4145).…”
Section: Discussioncontrasting
confidence: 47%
“…The HSCL-25 depression scale has previously been adapted and validated among adults in HIV-affected Ugandan communities (Bolton et al, 2003; Kaida et al, 2014). Average scores were generated for depression (15 item) and anxiety (10 item) subscales; higher scores indicating greater severity.…”
Section: Methodsmentioning
confidence: 99%
“…Rates of depression and anxiety are high among women living with HIV/AIDS (Hatcher et al, 2012; Kaida et al, 2014). Depression among mothers with young children is associated with multiple negative child behavioral and emotional outcomes (Leis, Heron, Stuart, & Mendelson, 2014), cognitive deficits and developmental delays (Black et al, 2010), and malnutrition (Surkan, Kennedy, Hurley, & Black, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this cohort, 39% of women were depressed, with higher depression scores among pregnant and postpartum women [39] . While the rollout of Option B+ and other strategies to reduce perinatal transmission are important in supporting women to meet their reproductive goals and have uninfected children [40], supporting women’s mental and emotional health is also crucial to growing healthy families, communities, and populations.…”
Section: Introductionmentioning
confidence: 99%